miR-766-3p Targeting BCL9L Suppressed Tumorigenesis, Epithelial-Mesenchymal Transition, and Metastasis Through the β-Catenin Signaling Pathway in Osteosarcoma Cells - Zhang, Sheng; Chen, Hongtao; Liu, Wanshun; Fang, Le; Qian, Zhanyang; Kong, Renyi; Zhang, Qi; Li, Juming; Cao, Xiaojian (Frontiers in Cell and Developmental Biology, 2020)
Accumulating evidence has indicated that abnormal microRNAs (miRNAs) serve critical roles in carcinogenesis and development of osteosarcoma (OS). The purpose of the present study was to elucidate the relationship between miR-766-3p and development of osteosarcoma and explore the potential mechanism. In this study, we found that miR-766-3p was the most downregulated miRNA by analyzing GSE65071 from the GEO database. miR-766-3p was lowly expressed in OS tissue samples and cells, and high miR-766-3p expression repressed the malignant level of OS, including cell proliferation, EMT, migration and invasion in vitro and in vivo. B-Cell Lymphoma 9-Like Protein (BCL9L) was negatively associated with miR-766-3p expression in OS cells and tissue samples and was validated as the downstream target by luciferase reporter assay and western blotting. Rescue experiment indicated that BCL9L could restore the influence of miR-766-3p on OS cells. In addition, the β-Catenin/TCF-4 signal pathway was demonstrated to be related to the miR-766-3p/BCL9L axis. In summary, miR-766-3p, a negative regulator of BCL9L, plays the role of tumor metastasis suppressor via the β-catenin signaling pathway in the progression of OS.